2021
DOI: 10.3389/fped.2021.691131
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Tissue-Engineered Urethras for Large Urethral Defect Repair in a Rabbit Experimental Model

Abstract: Introduction: Tissue engineering is a potential source of urethral substitutes to treat severe urethral defects. Our aim was to create tissue-engineered urethras by harvesting autologous cells obtained by bladder washes and then using these cells to create a neourethra in a chronic large urethral defect in a rabbit model.Methods: A large urethral defect was first created in male New Zealand rabbits by resecting an elliptic defect (70 mm2) in the ventral penile urethra and then letting it settle down as a chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Previous preclinical studies have demonstrated that cell seeding is benefcial in urethral tissue engineering [19,[26][27][28][29][30]. Most importantly, the use of adipose-derived stromal/stem cells (ASCs) or smooth muscle cells has been shown to enhance angiogenesis and the formation of the urethral stromal tissue during the tissue regeneration, inhibiting the formation of urethral fbrosis [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous preclinical studies have demonstrated that cell seeding is benefcial in urethral tissue engineering [19,[26][27][28][29][30]. Most importantly, the use of adipose-derived stromal/stem cells (ASCs) or smooth muscle cells has been shown to enhance angiogenesis and the formation of the urethral stromal tissue during the tissue regeneration, inhibiting the formation of urethral fbrosis [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous preclinical studies have demonstrated that cell seeding is benefcial in urethral tissue engineering [19,[26][27][28][29][30]. Most importantly, the use of adipose-derived stromal/stem cells (ASCs) or smooth muscle cells has been shown to enhance angiogenesis and the formation of the urethral stromal tissue during the tissue regeneration, inhibiting the formation of urethral fbrosis [26][27][28][29]. Besides ASCs, several cell types have been utilized in urethral tissue engineering research, including fbroblasts [31,32], smooth muscle cells [27,33,34], stromal/stem cells [35][36][37][38] along with urothelial cells (UCs) [10,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, graft infection occurred in three patients. More recently, SIS was used for the repair of a large urethral defect in 22 male rabbits, both unseeded and seeded with UCs harvested noninvasively by washing the urinary bladder with saline solution [ 92 ]. The authors found that cell-seeded transplants were superior to unseeded ones in terms of the regeneration of a stratified epithelium similar to a native urethra.…”
Section: Tissue-engineered Urethra In the Case Of Hypospadiasmentioning
confidence: 99%
“…Using UCs obtained by bladder irrigation, Fossum and coworkers successfully restored urethral function in patients with severe hypospadias [27]. Preclinical studies in rabbits have shown that these cells have the potential to form a stratified urothelium for the repair of long urethral defects [28]. Overall, these studies have demonstrated that bladder irrigation is a viable and reliable source of UCs and is more likely to be accepted by patients in the clinical setting than bladder biopsy.…”
Section: Urinary Mucosal Keratinocytesmentioning
confidence: 99%